A substituição de projeto de software por um novo: um estudo de caso - Detoni, Thiago Arahn (2022)
Enterprise software needs to be constantly updated in order to keep it usable. These updates have their origin in correcting errors and mainly in new organizational demands. Over time, these demands generate a significant workload that tends to become increasingly complex than the first requirements elicited. For this reason, the organization providing the software may choose to continue updating the old product or make it obsolete and replace it with a new one. Identifying the ideal moment to carry out this migration involves, in addition to the costs of keeping the product obsolete for a while, the effort to develop a new one. This work addresses a case study that comprises fifteen years with two migrations of the software project. Due to the availability of the collection of activities performed by the development and support team, performed sequentially over time, the applicability of time series was possible. Furthermore, the historical base of the activities performed made it possible to use the time series decomposition to obtain its trend, seasonality, and noise. Time series decomposition indicated that there were many random events in the first migration while in the second, the team self-regulated, but even so, there were tension points. This study made it possible to identify a preliminary model whose purpose is to determine when to develop a new version of the software. The present work is initially structured by the bibliographic review, Chapter 2, aiming to review different contents already published, following the research procedures, Chapter 3, which report the stages of organization of the material, as well as its main methods. Consequently, the results and discussions are presented, Chapter 4, which aims to show what was discovered in the research, having relevant data obtained and synthesized. Finally, the conclusions are presented, Chapter 5.